2020
DOI: 10.1002/jee.20371
|View full text |Cite
|
Sign up to set email alerts
|

Linking personal and professional social responsibility development to microethics and macroethics: Observations from early undergraduate education

Abstract: Background Developing social responsibility attitudes in future engineers and computer scientists is of critical and rising importance. Yet research shows that prosocial attitudes decline during undergraduate engineering education. Purpose Influenced by the Professional Social Responsibility Development Model (PSRDM), this study explores the connection between undergraduate personal social responsibility attitudes and the development of professional social responsibility attitudes. We consider a wide range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…The implications for ethics teaching become apparent. Empirical research on the culture of engineering education (Cech, 2014;Godfrey, 2014;Godfrey & Parker, 2010;Schiff et al, 2021) confirms the valorisation of the technical and the marginalisation of the societal dimension of engineering. Tormey et al, (2015, p. 2) notes that students' declining moral reasoning is the outcome of the culture within their institution, as courses with ethical content are "swimming against the hidden cultural tide of the programme as a whole".…”
Section: Contending Paradigms Of Engineering Educationmentioning
confidence: 95%
See 1 more Smart Citation
“…The implications for ethics teaching become apparent. Empirical research on the culture of engineering education (Cech, 2014;Godfrey, 2014;Godfrey & Parker, 2010;Schiff et al, 2021) confirms the valorisation of the technical and the marginalisation of the societal dimension of engineering. Tormey et al, (2015, p. 2) notes that students' declining moral reasoning is the outcome of the culture within their institution, as courses with ethical content are "swimming against the hidden cultural tide of the programme as a whole".…”
Section: Contending Paradigms Of Engineering Educationmentioning
confidence: 95%
“…We are guided in the use of the concept of “culture” by the definition provided by Schein ( 1992 , p. 12) and popularised in engineering education research by Godfrey and Parker ( 2010 ), according to which culture is understood as a pattern of shared basic assumptions that the group learned as it solved its problems of external adaptation and internal integration, that has worked well enough to be considered valid, and therefore, to be taught to new members as the correct way to perceive, think, and feel in relation to those problems. As Godfrey ( 2009 , p. 3) points out, this definition focuses on “the deepest, unconscious level of basic beliefs and assumptions, which underpins the more visible cultural manifestations”.…”
Section: Multi-level Analysis Of the Challenges Of Engineering Ethics Educationmentioning
confidence: 99%
“…It is suggested that "a quantum awareness or concepts course" on the undergraduate level, if possible in the first year, "to introduce students to the field early" would be beneficial [83] (p. 18), and that new courses are already being developed [84]. At the same time, it is recognized that the teaching of technical students on the 'social' aspects of technologies is lacking [85][86][87][88][89][90]. Techno-determinism and techno-optimism are recognized as biased forms of reporting within the STEM education literature [91][92][93][94], as is evident as well within statements such as "the need for quantum workforce and a well-educated society with knowledge and attitudes towards the acceptance of QT is imminent" [95] (p. 1).…”
Section: Education and Quantum Technologiesmentioning
confidence: 99%
“…Indeed, given that students have different interests [96], adding the 'social' might broaden the interest into quantum. The mapping exercises might counter the recognized problem that the teaching of technical students in 'social' aspects is lacking [85][86][87][88][89][90] and that techno-determinism and techno-optimism are recognized as biased forms of reporting within the STEM education literature [91][92][93][94], which also seems to be evident in quantum policy views on education, as evident from statements such as "the need for quantum workforce and a well-educated society with knowledge and attitudes towards the acceptance of QT is imminent" [95] (p. 1). It is suggested that "a quantum awareness or concepts course" on the undergraduate level, if possible in the first year "to introduce students to the field early" would be beneficial [83] (p. 18).…”
Section: Quantum Technologies and Educationmentioning
confidence: 99%
“…Scholars contested that the current challenges in Teaching Engineering Ethics is deeply grounded in the culture of engineering which over-stresses technical knowledge while marginalizing the ethical and societal dimension of engineering (Jamison et al, 2014;Schiff et al, 2021). Students' perceptions are shaped by the binary cultural frame.…”
Section: Introductionmentioning
confidence: 99%